SISTEM PENILAIAN KINERJA GURU DALAM PROSES PENGAJUAN KENAIKAN PANGKAT - Beny R E Manu; Meiton Boru; Kornelis L (Universitas Nusa Cendana, 2016)
The development of information technology makes Department of Education, Youth and Sports Kupang began developing administrative systems using information technology. One of the administrative system required by the Department of Education, Youth and Sports Kupang is in the public and employees of sub-section had difficulty in calculating the data processing performance of teachers in the process of filing a promotion to the preparation of reports. Therefore we need a system that can facilitate the processing of data in an integrated manner, which is supported by the use of desktop-based system to facilitate the presentation of information and data promotion of teachers. In this study designed “An Application Calculation Of Assessment Teacher Performance For Process Increase Filing In Rank Teachers